Social-Emotional Difficulties in Irish Children Aged Five and Nine Years: A National, Longitudinal Study - Ann Swift; Roy McConkey; Philip Curry; Edurne Garcia Iriarte (MDPI AG, 2021)
A small proportion of children experience social-emotional difficulties from early childhood onwards. Longitudinal studies with nationally representative samples are needed to identify the prevalence and the characteristics of children and families persistently experiencing these difficulties. Secondary analysis of data collected on over 7500 Irish children and with the Strengths and Difficulties Questionnaire as the primary indicator, found that 6% of children when they were five year olds and 8% when they were nine-years, had above threshold scores that warranted further investigation. A smaller proportion-2.9% had elevated scores at both ages. Logistic regression analyses found that children with one or more developmental disabilities were up to six times more likely to have sustained difficulties. There were also significant associations with the lower education attainment of primary caregivers and the socio-economic deprivation of families. Primary caregivers and teachers reported higher conflict in their relationships with these children. Although the number of Irish children presenting with continuing social-emotional difficulties is small, they can present an ongoing and future societal cost in terms of the impact on family relations and demands placed on educational, health and social services. This study identified the children and families who are at greatest risk and for whom targeted early intervention services could be provided.